1971
DOI: 10.1029/wr007i002p00292
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of Base Flow Recession Curves and Parameters

Abstract: The Boussinesq equation is used to show that base flow recession is an exponential decay function. For a single peaked hydrograph, the storage delay factor Kb, the time for base flow to decrease by a factor of 10, is estimated. The parameter Kb is adjusted by trial so that surface flow, or the observed total flow minus base flow, is also an exponential decay function after the point of inflection on the hydrograph recession. Surface flow K• is so determined. For 22 basins in Illinois, dormant season K• ranges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 6 publications
0
52
0
Order By: Relevance
“…Shaw and Riha (2012) end the extracted recession 2 days before dQ/dt changes from negative to positive following a recession start. Some studies use the inflection point of the recession curve -the first day following a rainfall event for which the hydrograph is concave down -to identify the start of the extracted recession (Singh and Stall, 1971;Wittenberg and Sivapalan, 1999). A similar concavity criterion, paired with the requirement of decreasing flow, could also be used to define the end of a recession event.…”
Section: Identifying the End Of A Recession Event (C)mentioning
confidence: 99%
“…Shaw and Riha (2012) end the extracted recession 2 days before dQ/dt changes from negative to positive following a recession start. Some studies use the inflection point of the recession curve -the first day following a rainfall event for which the hydrograph is concave down -to identify the start of the extracted recession (Singh and Stall, 1971;Wittenberg and Sivapalan, 1999). A similar concavity criterion, paired with the requirement of decreasing flow, could also be used to define the end of a recession event.…”
Section: Identifying the End Of A Recession Event (C)mentioning
confidence: 99%
“…Szilagyi and Parlange, 1998;Peña-Arancibia et al, 2010), but studies can also be found that eliminated an interval between 1 and 10 days (Zecharias and Brutsaert, 1988a;Vogel and Kroll, 1992;Parlange et al, 2001;Malvicini et al, 2005;van Dijk, 2010;Wang and Cai, 2010). Singh and Stall (1971) divided the declining hydrograph at the inflection point and analyzed only the latter part to reduce influence of surface flows at the beginning of recession. Other studies have extended this restriction and used only recessions that started two days after the inflection point (Wittenberg and Sivapalan, 1999;Wang and Cai, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Also, other methods that use some form of hydrological reasoning have been developed without a physically based mathematical framework. Currently, the separation of baseflow from the streamflow hydrograph can be carried out utilising methods that can be grouped into the following four categories: (1) graphical separation (Sloto and Crouse, 1996), (2) recession analysis (Tallaksen, 1995), (3) conceptual models (Barnes, 1939;Singh and Stall, 1971;Furey and Gupta, 2001;Eckhardt, 2005;Huyck et al, 2005) and (4) recursive digital filters (Nathan and McMahon, 1990;Arnold and Allen, 1999).…”
Section: Introductionmentioning
confidence: 99%